Radioactive characterization of sand samples from Failaka Island in Kuwait - Jallad, Karim (2016)
Sand samples were collected from Failaka Island in the state of Kuwait for radioactive characterization. The activity concentrations of both natural and artificial radionuclides were determined using gamma (γ)-ray spectrometry. From the measured γ-spectra, radioactivity concentrations were determined for Uranium-238 (238U), Thorium-232 (232Th), Radium-226 (226Ra), Potassium-40 (40K), and Cesium-137 (137Cs). To evaluate the radiological hazard of the natural radioactivity on Failaka Island, the radium equivalent activity, the representative level index, the external hazard index, the internal hazard index, the absorbed dose, and the effective dose rate were calculated and compared with international approved values.